2017
DOI: 10.1590/1089-6891v18e-37633
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Broilers Fed Different Dietary Choline Sources and Levels

Abstract: Two experiments were carried out to evaluate the bioequivalence of a commercial phosphatidylcholine source (Biocholine™) as an alternative to choline chloride and the choline requirements of broilers of a fast-growth strain. In Experiment I, 672 broilers were fed four Biocholine™ levels (0, 100, 200, or 300 mg/kg) and three choline levels (200, 400, or 600 mg/kg) supplied as choline chloride between 4 and 28 days (d) of age. In Experiment II, 462 broilers received diets supplemented with 0, 200, 400, 600 or 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
(46 reference statements)
4
9
1
2
Order By: Relevance
“…In the present study, feed conversion and productive efficiency index of the vegetable choline supplemented groups gave results similar to birds supplemented with choline chloride 600 mg kg -1 , however, these indices were higher than those of the choline chloride 800 mg kg -1 group. The data found agree with those of Calderano et al (2015) and Farina et al (2017), who found similar results on performance of broilers when evaluating the substitution of choline chloride with vegetable choline. An assumption regarding the absence of significant effect on weight gain evaluation in the first week of age may also be based on yolk choline vitelline reserves, due the good reserves it has.…”
Section: Zootechnical Performancesupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, feed conversion and productive efficiency index of the vegetable choline supplemented groups gave results similar to birds supplemented with choline chloride 600 mg kg -1 , however, these indices were higher than those of the choline chloride 800 mg kg -1 group. The data found agree with those of Calderano et al (2015) and Farina et al (2017), who found similar results on performance of broilers when evaluating the substitution of choline chloride with vegetable choline. An assumption regarding the absence of significant effect on weight gain evaluation in the first week of age may also be based on yolk choline vitelline reserves, due the good reserves it has.…”
Section: Zootechnical Performancesupporting
confidence: 89%
“…An assumption regarding the absence of significant effect on weight gain evaluation in the first week of age may also be based on yolk choline vitelline reserves, due the good reserves it has. Farina et al (2017) related presence of approximately 6,800 mg kg -1 of choline in yolk, being sufficient to meet and supply the necessary choline reserves. Broilers supplemented with 800 mg kg -1 CC displayed worse feed conversion and feed intake, nevertheless, feed intake was not different from those of other treatments.…”
Section: Zootechnical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The main causes of perosis are deficiencies of manganese, zinc (Zoidis et al, 2020), choline (Farina et al, 2017) or biotin in a feed. However, most often in broilers, this disease is associated with a lack of manganese in feed, rapid weight gain of birds and high poultry density in the chicken coop (Greenacre, 2015;Priyanka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, existem alguns compostos à base de plantas que contêm quantidades significativas de colina em sua composição, sendo alternativas ao cloreto de colina na suplementação de colina para ração. Eles têm grandes quantidades disponíveis de fosfatidilcolina, fosfatidilinositol e fosfatidiletanolamina (Calderano, et al, 2015;Farina, et al, 2017), que devido à sua alta afinidade por receptores intestinais, fornecem maior biodisponibilidade da colina do que o cloreto de colina. Esses compostos vegetais são menos higroscópicos e não prejudicam a integridade de outras moléculas presentes nos nutrientes.…”
Section: Introductionunclassified